Characterization and antimicrobial properties of cotton fabric loaded with green synthesized silica nanoparticles - Muhammad Amir; Muhammad Sajid Ali Asghar; Saeeda Nadir Ali (Penerbit Universiti Kebangsaan Malaysia, 2024)
During the past decade, improvement in the functionality of textile materials has become an important research field due to their significant health and safety benefits. Here we report, simple and cost-effective green synthesis of silica nanoparticles from fibrous residue of sugarcane bagasse followed by investigating the applicability on cotton fabric. The characteristics of synthesized nanoparticles were determined by techniques including FTIR (exhibited characteristic peak at 791.01 attributed to vibration of Si-O and the absorption band at 1072.48 cm-1 owing to asymmetric vibration of Si-O-Si confirming the formation of SNPs), SEM (40±2nm), and XRD (Examined spectra with JCPDS 36-1451 indicate well-defined peaks of Silicon Oxide). Debye Scherrer equation was used to calculate the mean crystallite size (19.79 nm) of powder Silica NP sample at the full width half maximum (FWHM) of the diffraction peaks of 2Ɵ positions. Applicability of synthesized nanoparticles was determined by assessing thermal stability and antimicrobial property of treated and untreated cotton fabric. It was observed that silica nanoparticles coated fabric showed substantial thermal stability at 1 % Silica NPs comparatively treated with 2% and 3% silica NPs due to clustering phenomena. Antimicrobial property, confirmatory test as positive control of treated fabric shown substantial increased in antibacterial activity in solutions containing silica NPs as compared to the ethanol solution. Moreover, 76 green profiling score of synthesized method was evaluated by Analytical Eco-Scale tool.